A Stress-Coping Model of Mental Illness Stigma: I. Predictors of Cognitive Stress Appraisal - Rüsch, Nicolas (2009)
Stigma can be a major stressor for individuals with schizophrenia and other mental illnesses. It is unclear, however, why some stigmatized individuals appraise stigma as more stressful, while others feel they can cope with the potential harm posed by public prejudice. We tested the hypothesis that the level of perceived public stigma and personal factors such as rejection sensitivity, perceived legitimacy of discrimination and ingroup perceptions (group value; group identification; entitativity, or the perception of the ingroup of people with mental illness as a coherent unit) predict the cognitive appraisal of stigma as a stressor. Stigma stress appraisal refers to perceived stigma-related harm exceeding perceived coping resources. Stress appraisal, stress predictors and social cue recognition were assessed in 85 people with schizophrenia, schizoaffective or affective disorders. Stress appraisal did not differ between diagnostic subgroups, but was positively correlated with rejection sensitivity. Higher levels of perceived societal stigma and holding the group of people with mental illness in low regard (low group value) independently predicted high stigma stress appraisal. These predictors remained significant after controlling for social cognitive deficits, depressive symptoms and diagnosis. Our findings support the model that public and personal factors predict stigma stress appraisal among people with mental illness, independent of diagnosis and clinical symptoms. Interventions that aim to reduce the impact of stigma on people with mental illness could focus on variables such as rejection sensitivity, a personal vulnerability factor, low group value and the cognitive appraisal of stigma as a stressor.